Construction Of Islamic Character Education For Mtss Milbos Students Bogor Indonesia - Zikry Septoyadi; Vita Candrawati (Al-Abshar: Journal of Islamic Education Management, 2025)
According to researchers, teaching and learning activities at MILBoS are running well, but the school's quality needs to be improved. One key aspect is the need to improve teacher resources to improve learning quality. Teacher supervision and guidance of students are also needed, as are improvements to incomplete facilities, and closer relationships with students. Therefore, this research is urgently needed for innovation and solutions in the world of education. The study, "Management of Islamic Character Education for Students at MILBoS," is particularly interesting, especially in a boarding school environment. It will yield significant results that can contribute to research in the world of education. The Indonesian Child Protection Commission handled 1,885 cases in the first semester of 2018. Of these, 504 children became criminals, with drug abuse and theft leading the way, with the most cases being indecent acts (Source: Detik.com, accessed February 13, 2023). This research uses a qualitative and descriptive analytical approach. A descriptive approach is a research procedure that produces descriptive data in the form of written or spoken words from people, images, and observed behavior, rather than numbers. This descriptive approach is used to describe variables as they exist in a situation. Therefore, in this study, the researcher describes and analyzes the facts surrounding the management of Islamic character education at MTsS MILBoS. Informants are research subjects who can provide information about the phenomena/problems raised in the study. The informants in this study were the principal, teachers, and students at MTsS MILBoS. The researcher also used secondary data, in the form of data that can provide information relevant to the research objectives. The data collection tools used were observation, interviews, and documentation. In qualitative research, the collected and obtained data will be analyzed using a qualitative interactive model approach consisting of three stages: data reduction, data presentation, and conclusion drawing or verification. The research results show that the management of Islamic character education at MILBoS is running well because it has a very good VISION and MISSION: to form qurota a'yun and to shape leaders for pious people. They have practiced waking up at 3:00 a.m. and performing Tahajud prayers, fasting on Mondays and Thursdays, and Quran memorization sessions. MILBoS trains students to maintain the cleanliness of their rooms, practice language discipline, and practice prayer. MILBoS has a six-to-one system, where one teacher focuses on six students. MILBoS also includes storytelling before bed. The environment is very beautiful, with many teachers